2019
DOI: 10.7759/cureus.6208
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Stand-alone Lateral Lumbar Interbody Fusion for Lumbar Adjacent Segment Disease

Abstract: Study designBiomechanical cadaveric study ObjectiveTo compare biomechanical properties of a single stand-alone interbody fusion and a single-level pedicle screw construct above a previous lumbar pedicle fusion.Summary of background dataAdjacent segment disease (ASD) is spondylosis of adjacent vertebral segments after previous spinal fusion. Despite the consensus that ASD is clinically significant, the surgical treatment of ASD is controversial.MethodsLateral lumbar interbody fusion (LLIF) and posterior spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Kretzer et al [ 17 ] reported stand-alone cage significantly decreased ROM in all motion planes in a cadaveric study, and the addition of facet screws or pedicle screws did not show a significant improvement in stability. In a biomechanical study of L3/4 stand-alone lateral interbody fusion above a previous L4-S1 posterolateral fusion, Chioffe et al [ 8 ] reported that the L3/4 intervertebral ROM was significantly reduced by 50% or even more in all motion planes relative to intact condition, and stand-alone LLIF was a biomechanically sound option in treatment of adjacent segment disease without necessitating revision. However, biomechanical studies evaluating multilevel LLIF were particularly limited, with most studies including one level [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kretzer et al [ 17 ] reported stand-alone cage significantly decreased ROM in all motion planes in a cadaveric study, and the addition of facet screws or pedicle screws did not show a significant improvement in stability. In a biomechanical study of L3/4 stand-alone lateral interbody fusion above a previous L4-S1 posterolateral fusion, Chioffe et al [ 8 ] reported that the L3/4 intervertebral ROM was significantly reduced by 50% or even more in all motion planes relative to intact condition, and stand-alone LLIF was a biomechanically sound option in treatment of adjacent segment disease without necessitating revision. However, biomechanical studies evaluating multilevel LLIF were particularly limited, with most studies including one level [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, mostly biomechanical studies evaluating lateral interbody fusion were usually focused on one or two levels [ 4 , 7 , 8 ]. However, for patients with degenerative spinal scoliosis or multilevel lumbar disease, three or even more levels LLIF are necessary to effectively correct spinal deformity and completely decompress neural elements [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stress of cage-endplate interface is the main factor leading to cage subsidence [ 11 ]. Previous studies [ 19 , 65 , 66 ] supported the placement of cage on the vertebral epiphysis for interbody fusion, which can not only provide immediate postoperative stability, but also better reduce the incidence of cage subsidence. This is also confirmed by the results of the present study, where endplate stress decreases as the axial area of the cage increases.…”
Section: Discussionmentioning
confidence: 99%
“…Kretzer et al [ 37 ] compared the reduction of ROM at L2–3 and L4–5 in 4 conditions—stand-alone LLIF, bilateral pedicle screw fixation, and 2 facet screw systems—and concluded that all instrumentation decreased ROM compared to the intact spine, with no differences detected among the fixation techniques. In a model of adjacent segment disease, Chioffe et al [ 38 ] found in 6 cadaveric specimens that L3–4 stand-alone LLIF decreased adjacent segment motion by 56%. Finally, in a study that highlights the role of cage width, Pimenta et al [ 18 ] found that a stand-alone 26-mm wide cage provided similar stability to bilateral pedicle screws and rods and greater stability than TLIF with bilateral pedicle screws, as well as 18-mm wide LLIF with unilateral pedicle screws.…”
Section: Discussionmentioning
confidence: 99%